Therapeutic aphorisms for paranoid personality disorder and paranoid ideation treatment: psychological opposites and complementaries in brief therapy - Paoli, Bernardo (Frontiers in Psychology, 2024)
Background: In Brief Therapy (BT), aphorisms (As) have been considered a privileged element in therapeutic language; with a handful of words they arouse emotions and different perspectives. Theoretical proposal: In As, a specific structure - the implicit or explicit Symmetry of Opposites (SoO) - allows a surprise effect, which in turn allows a therapeutic effect. Therefore, a carefully selected SoO (based on psychological complementaries) allows the desired therapeutic reframing, that can be identified as a core goal of the psychotherapeutic intervention. Research question: Is it possible to identify As with a therapeutic value in treating Paranoid Personality Disorder (PPD) and high Paranoid Ideation (hPI) cases? Method: Starting from an initial collection of 369 original As created on the spot in 2,335 BT sessions, As used during on-line psychotherapy on 55 patients with PPD and/or an hPI measured with the SCL-90-R were identified. Results: 33 As were selected and organised according to effective and ineffective strategies, target of the BT intervention for PPD and hPI cases.